Penerapan Aplikasi Lynk.id dalam Pembelajaran Matematika Berbasis Kurikulum Merdeka untuk Meningkatkan Literasi Digital Siswa - Al Firhani, Zahwa Syifa; Sadieda, Lisanul Uswah; Arrifadah, Yuni (JRPM (Jurnal Review Pembelajaran Matematika), 2025)
Education in the digital era requires the integration of technology into learning to enhance students' digital literacy, which is crucial for addressing the challenges of globalization. The low level of digital literacy in Indonesia, including at SMP Negeri 1 Sidoarjo, makes it necessary to innovate, such as the Lynk.id application. Lynk.id is a link management platform developed to integrate various links into one platform and function as an adaptive e-learning tool for modern education. This research examines the implementation of Lynk.id in mathematics learning based on the Independent Curriculum with a focus on teacher activities, student activities, and student responses. Using a quasi-experimental design with two groups, data collection was conducted using tests, observations, and questionnaires. Pretest-posttest digital literacy scores were analyzed using the Independent Sample T-Test. The results showed that teacher activity scored 7.48 (very good), student activity averaged 7.35 (very good), and student responses scored 122.19 (very good). Furthermore, Lynk.id has been proven to increase students' digital literacy significantly. Thus, the integration of Lynk.id in Merdeka Curriculum mathematics learning can improve students' digital literacy.